Barriers to seeking health care among returning travellers with malaria: A systematic review. Issue 1 (16th November 2021) - Lu, Guangyu; Cao, Yuanyuan; Chai, Liying; Li, Yuping; Li, Shuying; Heuschen, Anna‐Katharina; Chen, Qi; Müller, Olaf; Cao, Jun; Zhu, Guoding
Abstract: Objective: To identify barriers to seeking health care among returning travellers with malaria with the aim of developing targeted interventions that improve early health care‐seeking behaviour, diagnosis and treatment. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines, we conducted a systematic review of published medical literature, selecting studies that investigated and reported barriers to seeking health care among returning travellers and migrants with malaria. In total, 633 articles were screened, of which four studies met the inclusion criteria after a full‐text review. Results: The four studies reported barriers to seeking healthcare among returning travellers in China, the United States, Thailand and the Dominican Republic. Three studies had an observational design. The identified barriers were summarised based on the appraisal delay, illness delay and utilisation delay stages. During appraisal delays, low awareness of malaria was the most significant factor. Once the patient assessed that he or she was ill, belonging to a specific minority ethnicity, being infected with P . vivax and receiving a low level of social support were predictors of delayed health care‐seeking. Finally, the most significant factor associated with utilisation delays was the monetary cost. Conclusion: The health care‐seeking behaviour of returning travellers with malaria should be further investigated and improved. Addressing the identified barriers and gaps in health care‐seeking behaviour among returning travellers with malaria, particularly among groups at high risk of travel‐associated infections, is important to prevent severe disease and deaths as well as secondary transmission and epidemics.